Muslim Millennial Youths Infusing Religious Moderation: A Case Study Approach to Investigate Their Attitude - Zulkipli Lessy; Miftahur Rohman (IAIN Ponorogo, 2022)
One of the challenges for nurturing moderate values is to tame our extremism and fanaticism for becoming tolerant belief as extremism and fanaticism oftentimes trigger a blind submission to the religion, which may lead the belief to conservatism and radicalism. This study aims to investigate the attitudes of Muslim millennial youths in Lampung Province in perceiving moderate religious values. Employing the qualitative research method with a case study approach, the research solicited 16 Muslim millennial youths from a variety of youth groups, such as members of student organizations (Organisasi Siswa Intra-Sekolah or OSIS and Kerohanian Islam or Rohis), nationalist youth organizations, Muslim Students Association (HMI), and Campus Dakwah Institute (LDK) to gather their perspectives about the intra-religious relationship, leadership, and gender equality. The purpose of collecting their perspectives is to identify whether these youths are moderate or semi-moderate or whether they are radicalism or conservatism. The findings showed that levels of religiousness among these Muslim millennial youths are generally moderate and fairly moderate. However, some youth respondents were reportedly categorized as conservatism due to their responses that seemingly supported the issue of anti-non-Muslim leadership and anti-intra-religious relations. The study recommends, therefore, that moderate religious values should be promoted among Muslim millenial youths so that conservatism can be eradicated in order to infuse tolerance, moderation, and assertiveness to differences.